Pengaruh Kesehatan Mental Ibu terhadap Status Gizi Anak di Indonesia - Pertiwi, Yuyu; Pardede, Elda L (Jurnal Ekonomi Kependudukan dan Keluarga, 2023)
Malnutrition in children is still a problem in low and middle-income countries, including Indonesia. This research aims to assess how the mother's mental health influences the child's nutritional status, measured by stunting and underweight status, in the short term (when the child is 0-5 years old) and long-term (when the child is 7-12 years old). Using the Indonesia Family Life Survey 2007 and 2014 data, the logistic regression results shows that children of mothers with mental health problem have a greater tendency to experience underweight nutritional status in both the short and long term. However, the influence of maternal mental health problem on children's stunting status is only evident in the long term. In addition, being males, did not consume protein, received exclusive breastfeeding, having mothers who are working are associated with a greater likelihood to be stunted and underweight. On the other hand, children with low birth weight, born from over 35 years mothers, having mothers with a height of more than 145 centimetres, living in a household with a higher per capita expenditure quintile, with adequate sanitation, and living in urban areas, are associated with a lower tendency for stunting and underweight.